Predicting the Influence of Climate Change on the Deterioration of Heritage Building Materials Using Photogrammetric Observations - Luisa Hdz-Gil; Luisa María Gil-Martín; Paz Fernández; Enrique Hernández-Montes (Applied Sciences)
This study presents a predictive model for the surface deterioration of construction materials exposed to climatic conditions. The model is applied to Santa Pudia calcarenite, the primary construction material used in the heritage buildings of Granada, Spain. Input data on material recession was obtained by using photogrammetric observations. Deterioration was measured in three heritage buildings located in different climatic zones. The methodology proposed enables the deterioration rate of building materials under specific climate conditions to be estimated by exclusively using photogrammetric data. The method was also validated in laboratory tests. The results can be applied to structural analysis and the long-term assessment of cultural heritage vulnerability in the context of future climate change. Notably, the findings indicate that in the case of Santa Pudia calcarenite, global warming slows down the deterioration process.